MENGULAS BOARDGAME “SI ANAK NAKAL” DENGAN MODEL INTERAKSI ANALISIS - Emmareta Fauziah; Achmad Sultoni (Narada : Jurnal Desain dan Seni, 2021)
More than 7 hours a day Generation Z interacts with devices, so less time is spent interacting directly with humans their age. This type of boardgame is a game that increases the interaction between players. To develop a board game, it is necessary to know the aspects and components contained in it. In the last few years, there have been boardgames featuring local fairy tales, one of which is “Si Anak Nakal” by Mahavira Studio. This game research has been carried out previously by Kelvin and Hantanto in 2019 entitled "Perancangan Ulang Brand Identity Board Game Si Anak Nakal". However, it focuses more on redesign based on an analysis of visual identity. While this study focuses on the analysis of all components contained in the game. The boardgame analysis was carried out using qualitative data analysis methods. This analysis method uses an analysis interaction model consisting of data collection with observation and documentation, data reduction, data presentation and drawing conclusions. The results of the research are the aspects and components contained in the "Si Na Naughty" boardgame.